Adrenocorticotropic hormone combined with vigabatrin as a second-line therapy for West syndrome - Souza, Luciana de Paula; Bufara, Danielle Caldas; Tensini, Tallulah Spina; Antoniuk, Sergio Antonio; Franklin, Gustavo L.; Crippa, Ana Chrystina de Souza (Arquivos de Neuro-Psiquiatria, 2025)
West syndrome is an epileptic encephalopathy for which combination therapies with adrenocorticotropic hormone and vigabatrin have emerged as new treatment options.To evaluate the clinical and electroencephalographic remission rates, tolerability, and relapse rates in patients with West syndrome who failed primary treatment and underwent sequential therapy with vigabatrin and adrenocorticotropic hormone.We included 39 patients with West syndrome from 2 specialized centers, aged 2 to 120 months. The patients were treated with intramuscular tetracosactide depot added to vigabatrin and were prospectively followed up for ≥ 1 year. The outcomes were clinical, and electroencephalographic remission rates at 7 and 30 days and 1 year following combined therapy initiation, progression to other epilepsy types, therapy tolerability, and relapse rates were recorded.Of the original sample, 71% of the subjects were boys, and 87% had a known etiology. The clinical and electroencephalographic remission rates were 46.1%, 94.8% (p = 0.001), and 74.1% (p = 0.01) at 7 and 30 days, and 1 year after the initiation of combined therapy, respectively. At the 1-year follow-up, adverse effects were observed in 86.0% and the relapse rate was 21.6%. After a median follow-up of 21 months, 73.6% of the patients developed epilepsy.Combined therapy demonstrated a favorable efficacy profile in achieving clinical and electroencephalographic remission but was associated with significant seizure relapse rates in the medium term. Thus, it represents a feasible option for patients in whom initial treatment has failed.
Keywords: Spasms, Infantile; Adrenocorticotropic Hormone; Vigabatrin